Exploring the Influence of Purpose-Driven Culture, Work-Life Integration, and Digital Competency on Gen Z Employee Retention - Sihite, Mislan; Damanik, Lisa Gresti Sella (International Journal of Business, Law, and Education, 2025)
This study investigates the influence of purpose-driven culture, work-life integration, and digital competency on Gen Z employee retention in the modern workplace. As Gen Z increasingly becomes a dominant workforce demographic, understanding the factors that shape their intention to stay within organizations is critical for HR strategy and organizational sustainability. Using a quantitative approach, data were collected through an online structured questionnaire from a sample of Gen Z employees across various industries. The data were analyzed using multiple linear regression via SPSS. Results revealed that all three independent variables—purpose-driven culture, work-life integration, and digital competency—had significant and positive effects on employee retention intention. These findings highlight the need for organizations to align with generational values, provide supportive and flexible work environments, and enhance digital capabilities to improve retention rates. The study offers practical and theoretical implications for managing Gen Z talent and building a resilient, future-ready workforce.